Perineal Distensibility Using Epi-no in Twin Pregnancies: Comparative Study with Singleton Pregnancies. (27th March 2014) - Kubotani, Juliana Sayuri; Moron, Antonio Fernandes; Araujo Júnior, Edward; Zanetti, Miriam Raquel Diniz; Soares, Vanessa Cardoso Marques; Elito Júnior, Julio
Abstract : The aims of this study were to compare perineal distensibility between women with twin and singleton pregnancies and to correlate these women's perineal distensibility with anthropometric data. This prospective cross-sectional case-control study was conducted among nulliparous women, of whom 20 were pregnant with twins and 23 with a single fetus. Perineal distensibility was evaluated in the third trimester by means of Epi-no, which was introduced into the vagina and inflated up to the maximum tolerable limit. It was then withdrawn while inflated and its circumference was measured. The unpaired Student's t -test was used to compare perineal distensibility in the two groups and Pearson's correlation coefficient (r ) was used to correlate the pregnant women's perineal distensibility with their anthropometric data. There was no difference in perineal distensibility between the twin group (16.51 ± 2.05 cm) and singleton group (16.13 ± 1.67 cm) (P = 0.50 ). There was a positive correlation between perineal distensibility and abdominal circumference (r = 0.36 ; P = 0.01 ). The greater the abdominal circumference was, the greater the perineal distensibility was, regardless of whether the pregnancy was twin or singleton.